Pelatihan kepada Masyarakat dalam Menjaga Makna Kearifan Lokal, Nilai Sejarah, dan Adat Khas Tradisional Masyarakat Melayu Peninggalan Kerajaan Sriwijaya - Anggun Widiya; Lesi Hartati; Lilis Puspitawati; Rilla Gantino; Meifida Ilyas (Yumary: Jurnal Pengabdian kepada Masyarakat, 2021)
Purpose: This community service aimed to train generations to preserve the traditional house. Limas is one of the most famous houses among the traditional houses found in Palembang, famous for the patterns, shapes, and density of the art of carving in them along with the sparkling gold perado paint, which means glory and arrangement. Methods: The methods applied were lectures, direct practice, and interviews. Result: The role of government, students and students is crucial in preserving the historical value of the customs of the local community. Conclusion: The community still faces many obstacles that make the value of cultural diversity rarely socialized, even though this historical value is vital and does not exist in provinces outside Palembang.